Evaluasi Pelaksanaan Pendidikan Karakter di Pondok Pesantren Darul Ma'rifat Sumber Cangkring-Gurah Kediri - Tsani, Iskandar (Didaktika Religia, 2013)
This study attempts to evaluate the implementation of character education at pesantren Darul Ma’rifat Sumber Cangkring Gurah Kediri. Using qualitative approach, this study presents a natural and objective illustration of the problem. The data are analyzed based on inductive qualitative analysis. The analysis comes up with the conclusion that: 1) the implementation of character education at the Pesantren Darul Ma’rifat starts from the formulation of the objective of pesantren and then implemented through discipline to the students on their daily life. 2) The effectiveness of the implementation of character education can be seen from the structure of discipline implemented in this institution through several stratifications that exist in this institution that can be carried out effectively.